PREECLAMPSIA DURING PREGNANCY AS A PRESSING PROBLEM IN OBSTETRICS: CAUSES, DIAGNOSIS AND TREATMENT - Bakhodirova Rukhsora Akhtamzhonovna (Web of Journals Publishing, 2026)
Preeclampsia remains one of the most pressing and challenging issues in modern obstetrics, being a leading cause of maternal and perinatal morbidity and mortality. This pregnancy complication is characterized by a multifactorial etiology, complex pathogenetic mechanisms, and a variety of clinical manifestations, which complicates early diagnosis and timely treatment. This article examines current understanding of the causes of preeclampsia, its main pathogenetic components, clinical presentation, and diagnostic criteria. Particular attention is paid to current approaches to the management of pregnant women with preeclampsia, principles of drug therapy, and the prevention of severe complications. A summary of current data highlights the importance of early identification of risk factors and a comprehensive, interdisciplinary approach to preeclampsia treatment to improve pregnancy outcomes for both mother and fetus.
Keywords: Preeclampsia; pregnancy; obstetrics; arterial hypertension; pregnancy complications; diagnosis; treatment; maternal and perinatal morbidity.